2003
DOI: 10.2527/2003.81112741x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of consumer sensory ratings, marbling score, and shear force value to consumer acceptance of beef strip loin steaks

Abstract: Logistic regression was used to quantify and characterize the effects of changes in marbling score, Warner-Bratzler shear force (WBSF), and consumer panel sensory ratings for tenderness, juiciness, or flavor on the probability of overall consumer acceptance of strip loin steaks from beef carcasses (n = 550). Consumers (n = 489) evaluated steaks for tenderness, juiciness, and flavor using nine-point hedonic scales (1 = like extremely and 9 = dislike extremely) and for overall steak acceptance (satisfied or not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
95
1
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(103 citation statements)
references
References 26 publications
3
95
1
4
Order By: Relevance
“…data). These results were similar to those of Platter et al (2003), where a logit analysis estimated that sensory scores correctly classified 78 to 79% of beef samples into 'unsatisfied' or 'satisfied' categories.…”
Section: Sensory Scores and Allocation To Gradessupporting
confidence: 76%
See 1 more Smart Citation
“…data). These results were similar to those of Platter et al (2003), where a logit analysis estimated that sensory scores correctly classified 78 to 79% of beef samples into 'unsatisfied' or 'satisfied' categories.…”
Section: Sensory Scores and Allocation To Gradessupporting
confidence: 76%
“…In a recent study, Platter et al (2003) calculated the accuracy of sensory scores for tenderness, juiciness and flavour to predict 'unsatisfied' or 'satisfied' categories for beef striploin samples. In the present study, the accuracy for tenderness, juiciness, like flavour and overall acceptability to predict 'unsatisfactory' or better than 'unsatisfactory' grades varied between 77 and 83% correctly classified for Australian consumer, whereas for Korean consumers, the corresponding accuracies ranged from 67 to 80% correctly classified (J. M. Thompson, unpubl.…”
Section: Sensory Scores and Allocation To Gradesmentioning
confidence: 99%
“…The tenderness of meat from bulls has been reported to be lower than that of steers and to be more variable (Peachey et al, 2002;Maher et al, 2004). However, on the basis of the relationship published by Platter et al (2003), the WBSF values of bulls of both breeds in the present study would indicate relatively high acceptability in relation to tenderness.…”
Section: Discussionmentioning
confidence: 41%
“…Although the meat color of yak was deeper, the tenderness measured by shear force value in the yak meat was unsatisfying. These two indexes are the most important quality attributes affecting purchase decision of consumers (Huffman et al, 1996;Miller et al, 2001;Platter et al, 2003). Failla et al (2004) found that the primitive cattle breeds in Europe usually have more pH value, higher shear force value, better water-holding capacity and deeper flesh color than modern beef breeds.…”
Section: Discussionmentioning
confidence: 99%